Identification of a subpopulation of long-term tumor-initiating cells in colon cancer. Issue 8 (25th August 2020) - Peng, Linglong; Xiong, Yongfu; Wang, Rong; Xiang, Ling; Zhou, He; Gu, Haitao
Abstract: Long-term tumor-initiating cells (LT-TICs) are viewed as a quantifiable target for colon cancer therapy owing to their extensive self-renewal and tumorigenic and metastatic capacities. However, it is unknown which subpopulation of colon cancer cells contains LT-TICs. Here, based on the methods for isolating and identifying cancer stem cells (CSCs) and the functional features of LT-TICs, we aimed to identify a subpopulation of LT-TICs. Among the six cell lines assessed, our results showed that CD133 and CD44 coexpression was only detected in HCT116 and HT29 cell lines. In HCT116 and HT29 cells, CD133 + CD44 + cells not only shared the extensive tumorigenic potential of LT-TICs but also functionally reproduced the behaviors of LT-TICs that drive tumor metastasis (TM) formation, suggesting that CD133 + CD44 + cells are a typical representation of LT-TICs in colon cancer. Mechanistically, the enhanced capacity of CD133 + CD44 + cells to drive metastasis involves the up-regulated expression of Wnt-, epithelial–mesenchymal transition (EMT)-, and metastasis-related genes in these cells. Additionally, CD133 + CD44 + cells presented significant chemoresistance compared with corresponding nontumorigenic CD133 − CD44 − cells following exposure to oxaliplatin (OXLP) or 5-fluorouracil (5-FU). Accordingly, CD133 + CD44 + cells contained lower reactive oxygen species (ROS) levels than CD1133 − CD44 − cells, and the low ROS levels in CD133 + CD44 + cells were related to the enhancement of antioxidant defense systems. More importantly, CD133 + CD44 + cells developed less DNA damage after exposure to chemotherapeutics than CD133 − CD44 − cells. In conclusion, we identified a subpopulation of LT-TICs in colon cancer.